2004
DOI: 10.1074/jbc.m404319200
|View full text |Cite
|
Sign up to set email alerts
|

The Presequence Translocase-associated Protein Import Motor of Mitochondria

Abstract: Transport of preproteins into the mitochondrial matrix requires the presequence translocase of the inner membrane (TIM23 complex) and the presequence translocase-associated motor (PAM). The motor consists of five essential subunits, the mitochondrial heat shock protein 70 (mtHsp70) and four cochaperones, the nucleotide exchange-factor Mge1, the translocase-associated fulcrum Tim44, the J-protein Pam18, and Pam16. Pam16 forms a complex with Pam18 and displays similarity to J-proteins but lacks the canonical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(32 citation statements)
references
References 44 publications
(68 reference statements)
3
29
0
Order By: Relevance
“…Previous analyses indicated that Pam16 and Pam18 could form a heterodimer (18,19). Consistent with these findings, we found that upon mixing equimolar amounts of full-length Pam16 and Pam18, Ͼ75% of Pam16 was coimmunoprecipitated with antibodies specific for Pam18 (Fig.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Previous analyses indicated that Pam16 and Pam18 could form a heterodimer (18,19). Consistent with these findings, we found that upon mixing equimolar amounts of full-length Pam16 and Pam18, Ͼ75% of Pam16 was coimmunoprecipitated with antibodies specific for Pam18 (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Pam16 is not capable of stimulating Ssc1's ATPase activity and thus, is not a functional J protein partner of Ssc1 (19). However, whether the absence of this activity is an important aspect of Pam16's function is not known.…”
Section: The Absence Of a Functional J Domain In Pam16 Is Not Functiomentioning
confidence: 99%
See 3 more Smart Citations